Pengaruh Penggunaan Soil Stabilization Terhadap Sifat Mekanik Beton Dengan Agregat Halus Berkadar Lumpur Tinggi - Muhammad Gilang Indra; Ismeddiyanto Ismeddiyanto; Zulfikar Djauhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This research was conducted to identify soil stabilization effect on mechanical properties of concrete with high mud content. According to SNI 03-2461-2002 code, the fine aggregate should must contain mud more than 5% of as weight. In this research, soil stabilization of 1% from mud weight was added to concrete mixtures. The percentages of mud added to the concrete mixture in this research were 5%, 10%, 15%, 20% and 23%. A 15x30 cm cylinder is curing in normal water for 28 days to study its compressive strength, tensile strength and elasticity modulus with expectation of 20 MPa in the concrete quality. The result of the research shows an optimum increase in the compressive strength to the concrete with 20% variation mud content. By adding the soil stabilization, compressive strength of the concrete is increased by 30.14% compared to a concrete without the soil stabilization. The value of tensile strength of concrete with 5% variation mud content added soil stabilization lower by 2.60% compared to a variations of a concrete without mud content. The value of the elasticity modulus of concrete with 23% variation mud content added soil stabilization lower by 152.34% compared to a variations of a concrete without mud content. This research concludes that a high mud level concrete with soil stabilization has a higher concrete quality compared to the a high mud level concrete without soil stabilization.Keywords : Compressive strength, tensile strength, elasticity modulus, soil stabilization, mud